Therapeutic efficacy of SJA6017, a calpain inhibitor, in rat spinal cord injury - (:unkn) unknown (ELSEVIER SCI LTD, 2008)
Apoptosis is an important element of the secondary processes that occur after spinal cord injury. Calpain and caspases are key proteases in apoptotic death. We evaluated the neuroprotective effects of SJA6017 (a calpain inhibitor) and measured functional recovery in a rat spinal cord injury model. Thirty Wistar albino rats were divided into three groups of 10 animals each: sham-operated (group 1), trauma control (group 2) and trauma-plus-SJA6017 treatment (group 3). Spinal cord trauma was produced in the thoracic region of the animals. Rats in group 3 received SJA6017 1 min after trauma. Treatment efficacy was evaluated after injury using light microscopy and TUNEL staining. Neurological performance was assessed using a inclined plane and a modified version of the Tarlov's grading scale. Group 2 rats showed moderate traums with widespread edema, hemorrhage, vascular thrombi and necrosis 24 h after injury. Group 3 rats had significantly reduced tissue injury and apoptosis. Tarlov scores revealed that group 3 rats also had ameliorated recovery of limb function. Our results demonstrate that treatment with SJA6017 reduces apoptotic cell death, preserves spinal cord tissue and improves functional outcome. Treating calpain-induced apoptosis with this agent may be a feasible therapeutic strategy for patients with spinal cord injury. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: apoptosis; calpains; programmed cell death; spinal cord injury; ACTIVATED NEUTRAL PROTEINASE; NEURONAL CELL-DEATH; CYTOSKELETAL PROTEINS; ALZHEIMERS-DISEASE; MOUSE MODEL; APOPTOSIS; EXPRESSION; NEUROPROTECTION; PROTEOLYSIS; BRAIN